The cheetahs of the Northern Tuli Game Reserve, Botswana: population estimates, monitoring techniques and human-predator conflict - Brassine, Eleanor I (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2015)
Remaining viable cheetah (Acinonyx jubatus) populations in Africa are threatened by direct persecution through conflict with farmers and habitat degradation and fragmentation. Botswana is considered a stronghold for free roaming cheetahs in Africa, yet the country has had relatively limited research on its cheetahs, and information from the east of the country is lacking. Data on the current status of populations is thus required to make informed management decisions. My study provides estimates of population density, abundance, distribution and status for the demographically open cheetah population of the Northern Tuli Game Reserve (NOTUGRE) in Botswana. The effectiveness of two population monitoring methods, namely camera trapping and a photographic survey, were also investigated. Moreover, I report on the level of conflict between livestock farmers and predators on rural communal farmlands within and adjacent to NOTUGRE. Data were collected between May 2012 and November 2013. Results indicate a low population density of 0.61 Â± 0.18 adult cheetahs per 100 kmÂ² and a minimum population size of 10 individuals (nine adults and one cub). Camera traps placed at cheetah scent-marking posts increased detection rates and provided ideal set up locations. This approach, together with Spatial Explicit Capture- Recapture (SECR) models, is recommended for future studies. The long-term studies that are required to better understand the status of cheetahs in Botswana do not exist. Thus, photographic surveys may provide an alternative method for providing baseline data on population numbers, distribution and demography. The third aspect of my study gathered information on levels of livestock loss and human tolerance of predators through the use of interviews (n = 80). Conflict with subsistence farmers is a concern as livestock depredation is relatively high (9.1% of total livestock owned) and farmers had an overall negative attitude towards conservation of large predators. My results suggest that human-predator conflict in this area is more complex than the direct financial loss from depredation. Hence, reducing depredation rates alone is unlikely to change farmer tolerance of wildlife on farmlands. Improved, responsible farm management, including self-responsibility for livestock rearing, and positive appreciation for wildlife are necessary. The NOTUGRE cheetah population requires further research to understand possible threats to the population. Furthermore, a better understanding of the connectivity between cheetahs of NOTUGRE, South Africa and Zimbabwe is required. The number of cheetahs within NOTUGRE is too small to sustain a viable population, hence conserving cheetahs outside of the protected area should be a priority for the conservation of the population. This can only be achieved through assistance and involvement from national authorities, local people and conservation organisations.
Keywords: Cheetah -- Botswana; Northern Tuli Game Reserve; Animal populations -- Botswana